Cash for childcare schemes in the Nordic welfare states: diverse paths, diverse outcomes. Issue 1 (1st January 2016) - Duvander, Ann-Zofie; Ellingsæter, Anne Lise
ABSTRACT: Recent family policy developments may blur conventional family policy typologies. While policies in some European welfare states are shifting away from strong male breadwinner regimes towards work–family reconciliation, the adding of cash for childcare (CFC) benefits in Nordic earner-carer welfare states points in the opposite direction. How can we understand growing family policy hybridisation? Comparison of CFC schemes in the five Nordic countries is the empirical basis of the discussion here – what does the insertion of such a familistic policy measure actually mean? The analysis displays diverse national policy processes and policy outputs and wide variation in parents' responses to this policy incentive. Reforms have been subject to conflicts and amendments to different degrees, and impact has been shaped by their institution at different times distinguished by mothers' varying access to childcare services and labour markets. We conclude that conceptualisation of CFC schemes needs to be contextualised in relation to political dynamisms and opportunity structures.